2004
DOI: 10.31899/hiv2.1040
|View full text |Cite
|
Sign up to set email alerts
|

Combining community approaches and government policy to reduce HIV risk in the Dominican Republic

Abstract: The Population Council is an international, nonprofit, nongovernmental institution that seeks to improve the well-being and reproductive health of current and future generations around the world and to help achieve a humane, equitable, and sustainable balance between people and resources. The Council conducts biomedical, social science, and public health research and helps build research capacities in developing countries. Established in 1952, the Council is governed by an international board of trustees. Its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…As such, norms not only shape perceptions, but change attitudes that are conducive to condom use. This result provides further evidence of the importance of a community approach which promotes workplace solidarity and the empowerment of female sex workers for the prevention of HIV (Kerrigan et al . 2004).…”
Section: Discussionmentioning
confidence: 66%
“…As such, norms not only shape perceptions, but change attitudes that are conducive to condom use. This result provides further evidence of the importance of a community approach which promotes workplace solidarity and the empowerment of female sex workers for the prevention of HIV (Kerrigan et al . 2004).…”
Section: Discussionmentioning
confidence: 66%
“…It is hoped that by highlighting these important points in the sensitisation trainings with bar managers/owners, female sex workers will be able to redefine the social contract of sex work and end the routine practice of clients becoming violent towards women if they refuse to have sex with clients after drinking the alcohol purchased for them. Prior work has demonstrated the utility of sex workers and bar managers/owners signing a literal social contract agreeing to promote the health and wellbeing of sex workers within each establishment (Kerrigan et al 2004). The social contract in this context will articulate that managers and other sex workers should intervene and press charges against clients who become violent towards a woman, even if she consumed the client’s alcohol and refused to have sex with him.…”
Section: Discussionmentioning
confidence: 99%
“…Their educational materials featuring a Dominican sex worker called Maritza have been particularly successful as a peer education tool in addressing strategies such as negotiating and eroticising condom use with clients, refusing drunk, high or violent clients and keeping the client interaction as safe as possible for the sex worker. 6,13 COIN was also influential in the formation of the Movimiento de Mujeres Unidas (MODEMU), a Dominican sex worker union run entirely by sex workers for sex workers, with whom we also worked to develop the current study protocol and instruments.…”
Section: Ngo Partners Working With Sex Workers In Santo Domingo and Cmentioning
confidence: 99%
“…2 In Mexico and the Dominican Republic, where the study reported here took place, unprotected sex between sex workers and their clients often translates into high HIV and STI rates. [3][4][5][6] The Dominican Republic has a high number of people in the sex trade per capita, with some 50,000 female sex workers in Santo Domingo alone. A 2005 Ministry of Health study reported that HIV prevalence among Santo Domingo sex workers was 3%, compared to 1.7% in the general adult population.…”
mentioning
confidence: 99%